Halide abstraction by Na[B{C6H3(CF3)(2)-3,5}4]: Synthesis and structural characterization of the rhodium(I) cations [(eta(6)-arene)Rh(PPh3)(2)](+) (arene = benzene, toluene) - Buttler, O; Al-Fawaz, A; Kays, D; Day, J; Ooi, L; Aldridge, S (2006)
Halide abstraction from [(Ph3P)2Rh(μ-Cl)] 2 by the sodium salt of the weakly coordinating [BArf4]- anion [Arf = C6H 3(CF3)2-3,5] in the presence of excess arene offers a convenient, high-yielding route to the half-sandwich cations [(arene)Rh(PPh3)2]+[BArf4]- [arene = benzene (1), toluene (2)]. Crystalline samples of 1 and 2 are isomorphous [a = 13.1270(2), b = 15.3030(2), c = 17.5760(3) Å, α = 74.620(1), β = 81.533(1), γ = 88.540(1)° for 1] and feature the arene ligand bound to the rhodium atom in η6 fashion. © 2006 Wiley-VCH Verlag GmbH and Co. KGaA.